The Cleveland Referendum on Street Railways - Bemis, Edward W. (Quarterly Journal of Economics, 1908)
The Cleveland Referendum on Street Railways1 Edward W. Bemis Edward W. Bemis Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 23, Issue 1, November 1908, Pages 179–183, https://doi.org/10.2307/1883973 Published: 01 November 1908